Ilmu dan Agama dalam Perspektif Filsafat Ilmu - Wijaya, Cuk Ananta (Jurnal Filsafat "WISDOM", 2006)
Science and religion, in their early development, came fromthe same resources and had the same purpose—human survival inthe universe. However, gradually, science separate from religionafter it found some method that made it established as thediscipline. Now, science is really different from religion in manyaspects, among other things: rationality, method, purpose, and theway in which they see realities. God was excluded from thescience. Religious argument does not sufficient for science.Although they different, it does not mean that they have no ameeting point in human civilization. Science, to a certain extent, isable to make religious understanding more rational and openminded.So also religion, to a certain extent, is able to makescience more near to its purpose, as it determined before—to makehuman being survive and happy in the universe. Therefore, scienceand religion are complementary to one another.